Disrupted normal ingestion during glucose intake modulates glucose kinetics in humans - Tsuji, Tadataka (Springerplus, 2015)
This study aims to reveal the importance of chemical senses in glucose kinetics and autonomic nervous activity by imposing interventions during glucose intake. The glucose-loading test was applied to seven healthy individuals. Three successive oral glucose-loadings induced a gradual downward shift in the blood glucose curves (BGC) together with increased salivary α-amylase activity (s-AMY) and positively correlated with satisfaction scores. On the other hands, adding a pleasant flavor given during the third trial increased the BGC to the same level as that during the first loading with decreased s-AMY value. Direct intragastric delivery of glucose or clipping the nose induced a downward shift in both BGC and serum insulin response curves (IRC), resulting in a decrease of the area under the BGC, positively correlated with the area under the IRC and satisfaction scores, respectively. The present study suggests that disrupted normal ingestion during glucose intake modulates glucose kinetics along with increased s-AMY values, indicating enhanced sympathetic nervous activity and favorable chemical senses are important in maintaining glucose kinetics.